2010
DOI: 10.3111/13696991003723999
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of switching to biphasic insulin aspart from human premix insulin in a US setting

Abstract: The application of treatment effect data derived from a Canadian cohort to the US setting was a limitation of the cost-effectiveness analysis. The findings of this cost-effectiveness analysis are not applicable to insulin-naïve diabetes patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The CDM has been used extensively to evaluate the cost-effectiveness of new therapies for the treatment of diabetes [4][5][6][7][8]. The model is also routinely used to inform reimbursement decisions, public health issues, resource planning, clinical trial design, and optimal patient management strategies [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The CDM has been used extensively to evaluate the cost-effectiveness of new therapies for the treatment of diabetes [4][5][6][7][8]. The model is also routinely used to inform reimbursement decisions, public health issues, resource planning, clinical trial design, and optimal patient management strategies [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…If not available, the approach contains 16 complete cost data sets from several countries, including Australia, 14 Canada, 15,16 China, 17 Czech Republic, 18 Germany, 19 Saudi-Arabia, 20 Sweden, 21,22 Switzerland, 23 Thailand, 24 the United Kingdom, 25,26 and the United States. 27-29 The user can select 1 of those cost data sets. When another cost data set is used, the 16 existing cost data sets can serve as comparator (to verify the cost data).…”
Section: Methodsmentioning
confidence: 99%
“…More than 1 source was found for some countries, including Canada, 15,16 Sweden, 21,22 the United Kingdom, 25,26 and the United States. 27-29 In comparisons to determine the influence of selecting an appropriate source, results showed that the selection of the appropriate source has some influence, but in most cases, it is very limited. For more details, see Appendix V.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…[111113] BIAsp 30 was demonstrated to be dominant over BHI 30 in the Saudi Arabian setting and was cost effective in the South Korean and US settings (table VII). …”
Section: Newer Concepts Of Practicementioning
confidence: 99%